Application of Cooperative Learning Model Think Pair Share Type to Increase Students' Self Confidence Islamic Religious Education Subjects - Nasrulloh, Muhammad Farid; Ma'ruf, Mochammad; Khotimah, Khusnul; Maksum, Mohammad Ja'far Sodiq (APPLICATION: Applied science in Learning Research, 2024)
The aim of this research is to find out how effective the application of Think, Pair, Share nature is in increasing the self-confidence of students in class IX in PAI subjects. The research method used uses quantitative research. The research carried out is quantitative research. The experiment in this research is a quasi experimental design type experiment. This research aims to measure the application of the Think, Pair, Share type cooperative learning model in increasing self-confidence student. The population of this study includes all class IX students of SMPN 1 Kunjang for the 2023/2024 academic year. Meanwhile, sampling was carried out using a purposive sampling technique and it was found that the research sample classes were students from classes IX-F and IX-G, consisting of 72 students with 36 students in each class. Data collection techniques were carried out using objective tests in the form of pretest and posttest assessments and non-tests in the form of self-confidence questionnaires, observations and interviews. Researchers used Levene's Test. In this study, the hypothesis test used was comparative using SPSS 26.00 for Windows to calculate the t test for two independent samples (Independent-samples t-test) and two interconnected samples (Paired-samples t-test). the application of the Think Pair Share (TPS) learning model is able to increase students' self-confidence in PAI subjects in class IX at SMP Negeri 1 Kunjang.